Ultrasound-assisted extraction of hydroxytyrosol and tyrosol from olive pomace treated by gamma radiation: process optimization and bioactivity assessment. Issue 7 (10th March 2023) - Madureira, Joana; Albuquerque, Bianca; Dias, Maria Inês; Pinela, José; Calhelha, Ricardo C.; Santos-Buelga, Celestino; Margaça, Fernanda M. A.; Ferreira, Isabel C. F. R.; Cabo Verde, Sandra; Barros, Lillian
Abstract : Optimization of the extraction conditions provides olive pomace extracts with improved bioactivities. Abstract : Ultrasound-assisted extraction (UAE) was used to recover hydroxytyrosol and tyrosol from olive pomace, a residue generated by the olive oil industry. The extraction process was optimized using response surface methodology (RSM), with processing time, ethanol concentration and ultrasonic power as the combined independent variables. The highest amounts of hydroxytyrosol (36 ± 2 mg g −1 of extract) and tyrosol (14 ± 1 mg g −1 of extract) were obtained after 28 min of sonication at 490 W using 7.3% ethanol as the solvent. Under these global conditions, an extraction yield of 30 ± 2% was achieved. The bioactivity of the extract obtained under optimized UAE was evaluated and compared with that of an extract obtained under optimal heat-assisted extraction (HAE) conditions in a previous work of the authors. Compared to HAE, UAE reduced the extraction time and the solvent consumption, and also led to higher extraction yields (HAE yield was 13.7%). Despite this, HAE extract presented higher antioxidant, antidiabetic, anti-inflammatory and antibacterial activities and no antifungal potential against C. albicans . Furthermore, HAE extract also showed higher cytotoxic effects against the breast adenocarcinoma (MCF-7) cell line. These findings provide useful information for the food and pharmaceutical industries in developing new bioactive ingredients, which may represent a sustainable alternative to synthetic preservatives and/or additives.